Academic Anxiety — A Curse for Academic Achievement of Adolescents A Reality or Myth - Gupta, Ratna; Awasthi, Om Prakash (JOURNAL OF INDIAN EDUCATION, 2013)
We all have experienced situations in our lives which have posed challenges for us. All the challenges and problems put us to stress and that results in anxiety. Adolescence is the most critical period of human life. The child experiences a number of changes in this transitional period. The adolescent has to change in old habits of childhood in home, school and society. The change over to new pattern of habits creates anxiety in adolescents. This anxiety is a catalyst for achievements or it works as a curse? This paper makes an effort to explore this question. The main aim of the study is to explore role of academic anxiety in academic achievement. For this purpose 160 adolescents comprising 80 males and 80 female studying in different schools of Bareily city were selected through random sampling technique. Tool employed for the purpose was Academic Anxiety Scale for children (AASC) by Dr. R.K. Singh. Role of Anxiety in achievement was found to be negative.